Opisna raziskava mnenj in stališč študentov zdravstvene nege ter kliničnih mentorjev glede ocenjevanja kliničnega usposabljanja - Meden, Edita (Obzornik zdravstvene nege, 2017)
Introduction: Unplanned assessment based on criteria that have not been precisely defined may result in overlooking an unsuccessful student, thus contributing to hazardous work in a clinical setting. The purpose of the research was to determine the views and opinions of clinical mentors and student nurses on the assessment of clinical practice. Methods: A quantitative descriptive method was used. 84 undergraduate nursing students participated in the online survey and 37 clinical mentors completed the printed version of the survey. Data collection took place from October to November 2015. Descriptive statistics, Chi-square test, Mann-Whitney U test and Pearson correlation coefficient were used in the analysis. Results: More clinical mentors than students believe that they should be thoroughly prepared for clinical practice (U = 790, p < 0.001). Pearson's coefficient of correlation (r = %0.215, p = 0.024) has shown that satisfaction with the assessment of all respondents is greater if the assessment is formative and not only summative. The hi-square test has shown that the respondents rated the assessment tool as satisfactory (n = 47, 43.5 %; x2 = 4.3, p =0.229). Discussion and conclusion: Most respondents are not satisfied with the methods of clinical practice assessment. They are aware of the weaknesses of the assessment tool. They also pointed out the time pressure component in mentoring students. The research contributes to a better understanding of the clinical practice assessment process.
Keywords: evaluation; medicinske sestre; mentoring; mentorstvo; nurses; nursing; vrednotenje; zdravstvena nega